2018
DOI: 10.1111/sjpe.12186
|View full text |Cite
|
Sign up to set email alerts
|

Political uncertainty and stock market volatility: new evidence from the 2014 Scottish Independence Referendum

Abstract: We investigate the impact of heightened political uncertainty in the run-up to, and after, the 2014 Scottish independence referendum. The conditional volatilities of stock returns of our Scottish index and the FTSE all share index are characterised by the same GARCH parameters for a sample ending in late 2013, but this no longer holds when estimation extends closer to the referendum. The relative volatility of Scottish companies' stock returns peaked when polls indicated the referendum result was 'too close to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…For the 2014 Scottish independence referendum, J γ,2 is significant at the 95% level for K=0 and at the 99.9% level for K=1 and 5. This is consistent with the conclusions of Darby et al (2019) and Acker and Duck (2015) that showed that the CAPM residuals are related to betting odds. However, we go further and demonstrate that there is still explanatory power in the betting markets when the additional Fama-French factors are controlled for.…”
Section: Significance Testssupporting
confidence: 92%
See 1 more Smart Citation
“…For the 2014 Scottish independence referendum, J γ,2 is significant at the 95% level for K=0 and at the 99.9% level for K=1 and 5. This is consistent with the conclusions of Darby et al (2019) and Acker and Duck (2015) that showed that the CAPM residuals are related to betting odds. However, we go further and demonstrate that there is still explanatory power in the betting markets when the additional Fama-French factors are controlled for.…”
Section: Significance Testssupporting
confidence: 92%
“…In this paper we seek to describe the relationship between these two types of markets in the weeks and months leading up to a political event. There are a small number of examples in the literature that study this question (see Manasse et al (2020), Hanna et al (2021, Acker and Duck (2015) and Darby et al (2019)). However, they consider only a single event and typically study only empirical relationships.…”
Section: Discussionmentioning
confidence: 99%
“…Acker and Duck (2015) find that the residuals of an estimated CAPM model are significantly positively related to several proxies for the likelihood of a vote to remain as part of the UK, one of which is a weighted sum of the Betfair exchange odds for 'No'. Similarly Darby et al (2019) study equities listed on the LSE that were headquartered in Scotland. They find that uncertainty betas help predict cross-sectional returns.…”
Section: Changes In the Composition Of Government Naturally Brings Ab...mentioning
confidence: 99%
“…More recent studies have looked at political uncertainty associated with the 2016 Brexit referendum (e.g. Hill et al, 2019) and the 2014 Scottish independence referendum (e.g., Darby and Roy, 2019) and reported evidence of a significant stock market impact.…”
Section: Literature Reviewmentioning
confidence: 99%